THE IMPLEMENTATION OF TEACHING WRITING AND ERROR ANALYSIS OF ENGLISH WRITING OF HEARING – IMPAIR STUDENTS - Ageung Darajat (IKIP PGRI Pontianak, 2014)
The objectives of research are describing the implementation of writing to hearing – impair students writing, error analysis, and the improvement needed in teaching and learning writing to hearing – impair students. The research was conducted at a senior high school with special needs program in Pontianak, West Kalimantan Province. It is qualitative research in form of case study. The data of this thesis were collected through observation, interview, document analysis, and audio and visual material or photograph. Data analyzing are based on qualitative analysis, and quantitative analysis. This research result shows that: (1) the implementation of teaching and learning writing to hearing – impair students comprises of five dimensions: the documents of teaching and learning available to writing lesson, the procedure of teaching and learning writing, the evaluation used in writing class, the class climate during teaching and learning writing, and difficulties in teaching and learning writing; (2) the errors analysis in writing are categorized into: misspelling word, missing word and incomplete word structure; and (3) improvement offered to the teacher in the writing class was providing more feedback to the students writing. Keyword: writing, hearing – impair students, error analysis, case study.